If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18(13y + 12) = -17 + 16(13y + 8) + -15(9y + 17) Reorder the terms: -18(12 + 13y) = -17 + 16(13y + 8) + -15(9y + 17) (12 * -18 + 13y * -18) = -17 + 16(13y + 8) + -15(9y + 17) (-216 + -234y) = -17 + 16(13y + 8) + -15(9y + 17) Reorder the terms: -216 + -234y = -17 + 16(8 + 13y) + -15(9y + 17) -216 + -234y = -17 + (8 * 16 + 13y * 16) + -15(9y + 17) -216 + -234y = -17 + (128 + 208y) + -15(9y + 17) Reorder the terms: -216 + -234y = -17 + 128 + 208y + -15(17 + 9y) -216 + -234y = -17 + 128 + 208y + (17 * -15 + 9y * -15) -216 + -234y = -17 + 128 + 208y + (-255 + -135y) Reorder the terms: -216 + -234y = -17 + 128 + -255 + 208y + -135y Combine like terms: -17 + 128 = 111 -216 + -234y = 111 + -255 + 208y + -135y Combine like terms: 111 + -255 = -144 -216 + -234y = -144 + 208y + -135y Combine like terms: 208y + -135y = 73y -216 + -234y = -144 + 73y Solving -216 + -234y = -144 + 73y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-73y' to each side of the equation. -216 + -234y + -73y = -144 + 73y + -73y Combine like terms: -234y + -73y = -307y -216 + -307y = -144 + 73y + -73y Combine like terms: 73y + -73y = 0 -216 + -307y = -144 + 0 -216 + -307y = -144 Add '216' to each side of the equation. -216 + 216 + -307y = -144 + 216 Combine like terms: -216 + 216 = 0 0 + -307y = -144 + 216 -307y = -144 + 216 Combine like terms: -144 + 216 = 72 -307y = 72 Divide each side by '-307'. y = -0.2345276873 Simplifying y = -0.2345276873
| 2.X-4=140 | | 2xX-4=140 | | 8(x+7)=-72 | | -13y-25y=16y-19 | | 3x+3-3=9 | | -15y=-23y+8-24y | | 3/4(x-2)=21 | | -12z+25z-23z=15z-16 | | v-1/v-4=7/4 | | 14y=-26+30y+29y-22y | | Graphy=3x-4 | | -8y=-12+18y+7y-13y | | 12/(x)-(5)/(4x) | | -4-6z=4z+56 | | 12/x-5/4x | | -x-3=-2x | | -14+28x+26x=16x-12+8x | | -14-28x+26x=16x-12+8x | | 91=7(1+2x) | | 2x+4=39-5x | | 24z+27+13z=25-9z-5z | | 3=16+(x+1) | | -x+4=-2x+6 | | 9-4y=-11-6y | | -3x+4=-4x+9 | | -x+5=-2x+7 | | 2x+4y=3c | | 15x^4-100x^3-11=0 | | 7x+2(x+9)= | | 4xX-6+2xX+6=183 | | 10xX+8xX+6=264 | | -3x-5=-4x-2 |